Dynamics of Development of Laser-Induced Structures on the Surface of a Titanium Alloy - Fomicheva, Iana; Druzhinin, Petr; Amler, Hans; Schuesslbauer, Wolfgang; Christiansen, Silke; Leuchs, Gerd (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
We investigated the dynamics of LSFL (Low Spatial Frequency LIPSS) evolution on the titanium alloy surface. To create them, 12 W picosecond 1.064 μm laser with a pulse repetition rate from 50 kHz to 500 kHz was used. For different laser repetition rate (500, 150, 100 and 50 kHz), the ranges of LSFL periods and peak Fluence of pulse (Fp) for which the maximum period is reached were determined. We also determined the laser parameters at which the resulting LSFL have good quality and uniformity, regardless of the initial surface roughness.
CRIS-Team Scopus Importer:2023-06-02
Keywords: HSFL; LIPSS; LSFL; surface patterning; Ti6Al4V; titanium alloy